Community Wisdom in the Classroom: Oral Histories as Pedagogical Tools in Brazilian Indigenous Schools - Clara Mendes; Felipe Souza; Livia Alves (Yayasan Adra Karima Hubbi, 2025)
Background. The effectiveness of oral corrective feedback (OCF) in language learning is influenced by learners’ comprehension and response to various OCF techniques. Therefore, it is essential for teachers to consider learners’ preferences for OCF strategies. Purpose. This quantitative study aimed to investigate the preferences of Thai as a foreign language (TFL) learner for ten commonly discussed types of OCF. Specifically, it examined whether these preferences are influenced by four learner variables: proficiency level, first language (L1), foreign language classroom anxiety (FLCA), and foreign language enjoyment (FLE). Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. The findings indicate that, regardless of proficiency level, L1, FLCA, or FLE level, learners prefer more explicit OCF techniques, such as metalinguistics feedback and explicit correction. However, Korean undergraduates scored lower in the majority of OCF strategies (i.e., ignoring, elicitation, recast, explanation, and public feedback) compared to the other participants. Conclusion. This study has significant implications for instructional practices in TFL settings and for L2 lecturers in the classroom. By understanding learners’ preferences for OCF, educators can tailor their instructional approaches to meet the specific needs of their students.